Pengaruh Pengelolaan Keuangan Dan Pelatihan Pegawai Terhadap Kinerja Keuangan Pada Suku Dinas Tenaga Kerja Transmigrasi Dan Energi Kota Jakarta Barat - Wahyu Dwi Widodo; Darma Wijaya; Fadli Ilyas (Tamilis Synex: Multidimensional Collaboration, 2024)
This study aims to analyze the influence of financial management on financial performance, to find out the effect of employee training on financial performance and the influence of financial management and employee training on financial performance in the Department of Manpower, Transmigration and Energy of West Jakarta City. This study uses a quantitative method. The number of samples in this study uses saturated sampling whose sampling technique of all population members is used as a sample, this study totals 50 employees. Data collection techniques are carried out by field studies, observations and questionnaires/questionnaires. The results of this study are according to the results of the t-test that financial management on financial performance in the West Jakarta City Transmigration and Energy Manpower Department based on the Financial Management Calculation (1,343) <table (2,012), then Ha is accepted and Ho is rejected, while the Effect of Employee Training on Financial Performance in the West Jakarta City Transmigration and Energy Manpower Department is based on the results of the Employee Training Calculation (2,070) table (2,012), then Ha was accepted and Ho was rejected and according to the results of the F test The influence of financial management and employee training on financial performance in the West Jakarta City Manpower, Transmigration and Energy Department. Based on the results of the first model F test, the F value of 4.254 is greater than the table F value of 3.18 with a significant level of 0.000 < 0.05 Therefore, simultaneously the variables of financial management and employee training have a significant effect on the variables of financial performance, the end of this study is based on the results of the R Square value (Coefficient of Determination) of 0.153 which means that Financial Management and Employee Training have a contribution level of 15.3% to Financial Performance simultaneously.